2013
DOI: 10.4236/fns.2013.48a012
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Major Hydrophilic and Lipophilic Antioxidants from Papaya Fruit to Total Antioxidant Capacity

Abstract: Several studies have shown that phenolic and carotenoid compounds protect against oxidative stress, reducing the risk of cardiovascular diseases and some types of cancers. The objective of this research was to determine the individual contribution of the main phenolic compounds from the papaya fruit skin and the individual contribution of main carotenoids from the pulp for total antioxidant capacity at four ripening stages; and the individual and combined radical scavenging ability used the essays DPPH (radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…According to Shahidi (2002) it was stated that positive and prominent correlation existed between catechin content and antioxidant activity in beach pea seed coats. As per finding of Sancho et al, 2013, some hydrophilic phenols and lipophilic phenols showed contribution towards total antioxidant activity in papaya fruit while others showed antagonistic effect. In conformity to the above results Yao et al, 2010 explained the existence of positive correlation in between total phenolics and antioxidant activity in seven different colored grains.…”
Section: Resultsmentioning
confidence: 99%
“…According to Shahidi (2002) it was stated that positive and prominent correlation existed between catechin content and antioxidant activity in beach pea seed coats. As per finding of Sancho et al, 2013, some hydrophilic phenols and lipophilic phenols showed contribution towards total antioxidant activity in papaya fruit while others showed antagonistic effect. In conformity to the above results Yao et al, 2010 explained the existence of positive correlation in between total phenolics and antioxidant activity in seven different colored grains.…”
Section: Resultsmentioning
confidence: 99%
“…The scavenging of 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) or diammonium salt radical cation (ABTS+; Sigma-Aldrich) was determined based on literature procedure ( Sancho et al, 2013 ). The 2.4 mM Potassium persulfate (2.4 mM) 7 mM ABTS (7 mM) were mixed at a ratio of 1:1, protected from light with aluminum foil, and allowed to react for 14 h at ambient temperature (22 °C) and then labelled as.…”
Section: Methodsmentioning
confidence: 99%
“…As results from the literature (Arnao 2000;Pérez-Jiménez et al 2008;Paśko et al 2009;Shalaby and Shanab 2013;Gayosso-García Sancho et al 2013), the mentioned methods should not be applied for the estimation of antioxidant properties of substances which themselves (or their oxidation products formed during neutralization of radicals) absorb in the range of the monitored wave length. The presence of such compounds in the measuring system falsifies the changes of absorbance resulting from the concentration decrease of the colored radical and makes the estimation of the real antioxidant activity of the examined compounds impossible.…”
Section: Introductionmentioning
confidence: 99%